Comparative efficacy and safety of six non-ergot dopamine-receptor agonists in early Parkinson's disease: a systematic review and network meta-analysis - Chen, Xiang-Ting; Zhang, Qian; Chen, Fei-Fei; Wen, Si-Yuan; Zhou, Chang-Qing (Frontiers in Neurology, 2023)
Background Non-ergot dopamine agonists (NEDAs) have been used as monotherapy or as an adjunctive therapy to levodopa for many years. Novel long-acting formulations of NEDAs including pramipexole extended-release (ER), ropinirole prolonged-release (PR), and rotigotine transdermal patch have been developed. However, there is no strong evidence that a given NEDA is more potent than another. We performed a systematic review and network meta-analysis to evaluate the efficacy, tolerability and safety of six commonly used NEDAs in early Parkinson's disease (PD). Methods Six NEDAs including piribedil, rotigotine transdermal patch, pramipexole immediate-release (IR)/ER, and ropinirole IR/PR were investigated. The efficacy outcomes including Unified Parkinson's Disease Rating Scale activities in daily life (UPDRS-II), motor function (UPDRS-III), and their subtotal (UPDRS-II + III), tolerability and safety outcomes were analyzed. Results A total of 20 RCTs (5,355 patients) were included in the current study. The result indicated that compared with placebo, all six investigated drugs had statistically significant differences in the improvement of UPDRS-II, UPDRS-III, and UPDRS-II + III (except ropinirole PR in UPDRS-II). There were no statistically significant differences between six NEDAs for the UPDRS-II and UPDRS-III. For UPDRS-II + III, the improvement of ropinirole IR/PR and piribedil were higher than that of rotigotine transdermal patch, and piribedil was higher than that of pramipexole IR. The surface under the cumulative ranking curve (SUCRA) indicated that piribedil resulted in best improvement in UPDRS-II and UPDRS-III (0.717 and 0.861, respectively). For UPDRS-II + III, piribedil and ropinirole PR exhibited similar improvement and both had high rates (0.858 and 0.878, respectively). Furthermore, piribedil performed better as monotherapy, ranking first in the improvement of UPDRS-II, III, and II + III (0.922, 0.960, and 0.941, separately). With regard to tolerability, there was a significant increase in overall withdrawals with pramipexole ER (0.937). In addition, the incidence of adverse reaction of ropinirole IR was relatively high (nausea: 0.678; somnolence: 0.752; dizziness: 0.758; fatigue: 0.890). Conclusions In this systematic review and network meta-analysis of six NEDAs, piribedil exhibited better efficacy, especially as monotherapy, and ropinirole IR was associated with a higher incidence of adverse events in patients with early PD.